Robótica educacional e pensamento computacional como uma metodologia para o ensino de algoritmos e programação - Cardoso, Carlos Costa (2023)
The teaching of Programming Logic presents itself as a common activity for teachers of courses in the areas of computing and information technology. This discipline is directly related to the success of students in technology courses, as the development of logical reasoning by each individual enhances program construction and problem-solving activities. The teaching of Programming Logic and Algorithms is often hampered, as many of the existing tools are linked to traditional teaching practices. For many students, initial problems in learning Algorithms and Programming Logic arise during the initial stages of teaching, when they need to understand and apply the abstraction related to programming and solving mathematical problems. The incorporation of constructionism linked to Educational Robotics and Computational Thinking in the teaching of Algorithms and Programming Logic can allow playful teaching, facilitating the understanding of school content, group work and critical thinking. The guiding question of this research is based on the question “How do Educational Robotics and Computational Thinking contribute to the teaching of Algorithms and Programming?”. Its general objective is to “Analyze the contributions of Computational Thinking and Educational Robotics as an enhancing methodology in teaching Algorithms in the discipline of Programming Logic”. The construction of this work was based on qualitative research of an exploratory nature, evaluating the teaching of Algorithms through a 40-hour blended workshop, using action research as a methodological path, using an initial questionnaire to characterize the participants and a diary board of students and teacher during the implementation of the workshop. The target audience for this research were students of the IT Technician course at IFMA-Campus Açailândia, classes 2020 and 2022, out of a total of 70 students. The participation of 41 students was obtained, which, through an initial questionnaire, demonstrated that 80.5% of the students liked the Programming Logic subject and found this subject important, and few students reported having had contact with Coding in Block or Educational Robotics. Regarding the logbooks, using descriptive analysis, it was observed that the teaching practices of Programming Logic and Algorithms using Computational Thinking and Educational Robotics, Block Coding and tools such as Tinkercad and PictoBlox, demonstrate be extremely relevant resources, guaranteeing the protagonism, motivation and fun of the students at the end of the workshop, highlighting the recovery of the essence of the Programming Logic discipline. Through the teacher's logbook, professional satisfaction was perceived in the students' participation, the advantages of this methodology, as well as the need for more time for practices, as well as also linking the use of traditional teaching using languages programming skills like C or Python after block coding. In the end, the Educational Product (MOOC) “Course of Educational Robotics and Computational Thinking in the teaching of Algorithms and Programming” was created, made available on the portal <pensandocomrobotica.com.br>, with a workload of 40 hours and certification, made available to all people. This dissertation is accompanied by the educational product, available at <http://educapes.capes.gov.br/handle/capes/731220>.